Intregrated electronice: analog and digital circuits and systems - Millman, Jacob (Tata McGraw-Hill, 2010)
Intregrated electronice: analog and digital circuits and systems / Millman, Jacob. -- New Delhi: Tata McGraw-Hill, 2010 621.381 M655 2nd ed. No. of Copies : 1